รูปแบบการพัฒนาสมรรถนะการสอนสำหรับครูทัศนศิลป์ในโรงเรียนระดับมัธยมศึกษา - ณัฐธิดา ภู่จีบ (จุฬาลงกรณ์มหาวิทยาลัย, 2016)
The purposes of this research were to 1) Analyze current and the desirable states of developing teaching competency for secondary school art teachers of 2) enhance the model of teaching competency development for visual art teachers of secondary schools. 3) to experience the use of the model of teaching competency development for the visual art teachers. Using 400 schools under the office of Secondary Education Service Area as a sample group, with visual art teachers as a key informant. The research instruments were questionnaire and interview. The data were analyzed by frequency, percentage, average, standard deviation , and index PNIModified. The research result indicates that 1.In recent circumstance, there are desirable conditions that could helps develop teaching competency for the art teachers, as a result, there are four patterns that above median range of priority need index. Which is, knowledge management , that has the most level of priority need, and following with training, coaching and mentoring system. It was also found that all five competencies in the high of priority need index. And by analyzing, it indicates that the first competency to develop were skills and professional development and lifelong learning. Next competency to enhance is knowledge, characteristics, and Ethical standards and values. In the topic of preferenced term of development model, it shows that to enhance knowledge and skill dimension, the most effective way were training, coaching, and knowledge management. For enhance the characteristic, the best way is by using knowledge management. Or even in the other case of enhancing ethical standards and values, the most prefered way is knowledge management combine with mentoring system. For Professional development and lifelong learning, it is better to use knowledge management, mentoring system, and training all together. 2. The development method is called "The Model of Teaching Competency Development for Visual Art Teachers of Secondary Schools" which scored the highest level in feasibility and suitability assessment conducted by focus group The model has seven important components, including : 1)Model’s name 2)Principle and emphasis 3)Model’s objective 4) Model’s core elements, which consist of 4 different elements. There are Coaching, Mentoring, Training and Knowledge Management. These 4 core elements are meant to develop 5 main competencies of Professional Knowledge, Skills, Characteristic, Ethical Standards and Values, and Development and Lifelong Learning. 5) Model’s supporting mechanic consist of 4 main parts which are Supporting, Self Development, Evaluate and Knowledge Management. 6) Model’s diagram and implementation. 7) Benefits 3. The result of experiment on applying this model on trails reflects that they have higher visual art teaching competency, with statistically significant at the level of 0.05. Suggestions on implementing research’s result are 1) implementing the model should be done on a well consideration of teacher’s circumstances, in order to set the appropriate timeframe of development. 2) Administration should prioritize and focus on the most suitable model that fits each of competency’s contexts, to achieve maximum efficiency and effectiveness. 3) There should be a continuity of using knowledge management process and ICT should be used to support. 4) There should be a pre-test to evaluate each of five competencies on the teacher before introducing them to the model, in order to organize a proper development model that compatible with each competencies character.